2019
DOI: 10.3389/fphar.2019.00621
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Cannabinoid Chemotypes: Structural Insights

Abstract: Cannabis has long been known to limit or prevent nausea and vomiting, lack of appetite, and pain. For this reason, cannabinoids have been successfully used in the treatment of some of the unwanted side effects caused by cancer chemotherapy. Besides their palliative effects, research from the past two decades has demonstrated their promising potential as antitumor agents in a wide variety of tumors. Cannabinoids of endogenous, phytogenic, and synthetic nature have been shown to impact the proliferation of cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 117 publications
(140 reference statements)
0
20
0
Order By: Relevance
“…The skin ECS contributes to the regulation of cell differentiation and proliferation through AEA and FAAH that maintain homeostasis through cannabinoid receptor signaling [37,51,124,153]. Both non-melanoma and melanoma skin cancer cells express CB1 and CB2 receptors, alongside other receptors that cannabinoids can activate [154,155]. Cannabinoids have revealed pro-apoptotic and anti-proliferative in various cancers such as prostate, digestive tract and breast carcinomas, with CBD demonstrating the strongest anti-tumor effects [156].…”
Section: Cannabinoids' Role In Skin Cancer and Its Associated Inflammmentioning
confidence: 99%
“…The skin ECS contributes to the regulation of cell differentiation and proliferation through AEA and FAAH that maintain homeostasis through cannabinoid receptor signaling [37,51,124,153]. Both non-melanoma and melanoma skin cancer cells express CB1 and CB2 receptors, alongside other receptors that cannabinoids can activate [154,155]. Cannabinoids have revealed pro-apoptotic and anti-proliferative in various cancers such as prostate, digestive tract and breast carcinomas, with CBD demonstrating the strongest anti-tumor effects [156].…”
Section: Cannabinoids' Role In Skin Cancer and Its Associated Inflammmentioning
confidence: 99%
“…Recent studies suggested that some cannabinoid-based treatments might have antitumor properties. [2][3][4][5] Cannabinoids were found to modulate key cell signaling pathways involved in the control of cancer cell proliferation and survival. [6][7][8] However, most of these studies utilized in vitro methods, a few were done in immune-competent animal models, and the data from human patients are anecdotal.…”
Section: Cannabis and Cancermentioning
confidence: 99%
“…Nevertheless, several studies have evaluated the antitumor effect of different types of CB2R molecules already used in cancer therapy for their well-established palliative effects. Several works have underlined that endogenous, phytogenic, synthetic cannabinoids, and modulators of endocannabinoid biosynthesis, are able to inhibit the proliferation of a wide spectrum of tumor cells with mechanism not totally unravelled [11]. Velasco, et al suggested at least four anticancer mechanisms: 1) the suppression of mitogenic signal; 2) the induction of apoptosis; 3) the inhibition of tumor angiogenesis; 4) induction of metastasis [11].…”
Section: Editorialmentioning
confidence: 99%
“…Several works have underlined that endogenous, phytogenic, synthetic cannabinoids, and modulators of endocannabinoid biosynthesis, are able to inhibit the proliferation of a wide spectrum of tumor cells with mechanism not totally unravelled [11]. Velasco, et al suggested at least four anticancer mechanisms: 1) the suppression of mitogenic signal; 2) the induction of apoptosis; 3) the inhibition of tumor angiogenesis; 4) induction of metastasis [11]. Concerning to CB2R agonists, among phytocannabinoid, morin, a flavonoid structurally closely related to quercetin, showed an apoptotic effect by a mechanism not fully resolved [10].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation